Analisis Dampak dan Tindakan Pencegahan Bullying Dikalangan Pelajar dalam Persepsi Hak Asasi Manusia - Karimah, Natiqatul; Jayanti, Olyvia Syafira Putri; Astari, Marsyadini; Nurhasanah, Nurhasanah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Bullying is any form of oppression or violence, which is done deliberately by a stronger person or group to intimidate or dominate others who are perceived as weaker. Both physical, verbal, and nonverbal bullying (spicy). Bullying often occurs in the school environment. This study uses a literature study study method. The main source of this research is research articles published on various sources, namely Google Scholar, Scopus, and Web of Science. The keyword used in literary livelihood is